1998
DOI: 10.1063/1.122720
|View full text |Cite
|
Sign up to set email alerts
|

“Contact epitaxy” observed in supported nanoparticles

Abstract: We have observed the formation of heteroepitaxial interfacial layers between silver nanoparticles and a single crystal copper surface by a phenomenon we term “contact epitaxy.” Upon depositing Ag nanoparticles (5–20 nm diameter) onto clean (001) Cu in an ultrahigh vacuum in situ transmission electron microscope, a thin (111)-oriented layer of Ag was detected at the interface between the substrate and particles. Molecular dynamics simulations reveal that the epitaxial layers form within picoseconds of impact, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 11 publications
2
74
0
1
Order By: Relevance
“…Moreover, stresses associated with defects caused by initial mismatching at the particle-particle interface might be sufficient to induce rotation of the crystallites into an aligned configuration. [43] It seems possible that such processes could also occur within aggregates, along with coherent restructuring at the particle-particle interfaces. [33,35,37,44] The latter could involve densification, and intra-aggregate reactivity and ripening.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, stresses associated with defects caused by initial mismatching at the particle-particle interface might be sufficient to induce rotation of the crystallites into an aligned configuration. [43] It seems possible that such processes could also occur within aggregates, along with coherent restructuring at the particle-particle interfaces. [33,35,37,44] The latter could involve densification, and intra-aggregate reactivity and ripening.…”
Section: Methodsmentioning
confidence: 99%
“…Similar observations of the epitaxial regrowth of a cluster melted upon impact have been reported for deposition of energetic Au [9,10] and Cu [7] clusters. Only partial epitaxy has been reported for large clusters deposited at low impact energies [8,9]. We find that the tendency to form an epitaxial island also depends on the potential used in the simulation.…”
Section: Computational Modelmentioning
confidence: 89%
“…It has been observed that the final state of a deposited cluster depends on the size and the incident energy of the cluster, with partial "contact epitaxy" characteristic for low-energy "soft landing" of large clusters and complete epitaxy characteristic for smaller and/or more energetic clusters [7,8,9,10]. Simulations of the film growth by cluster deposition revealed a strong dependence of the morphology of the growing film on deposition parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9] The organization of building blocks have been intensively explored, and a number of assembly methods have been demonstrated to achieve ordered arrays on various substrates.…”
Section: Introductionmentioning
confidence: 99%